Organizational Transformation through Change Management and Innovation Synergy: Theoretical and Practical Approaches - Abd. Rasyid Syamsuri; Revaldo Joy Pratama Zebua; Jhonatan Andro; Raffy Ahmad (Journal of Global Islamic Economic Studies, 2024)
This study aims to explain the concept of change management and innovation within the context of increasingly dynamic modern organizations. Change management is a systematic approach designed to handle the process of transitions or transformations that occur within organizations, whether structural, technological, or cultural. On the other hand, innovation involves the development of new and creative ideas that can be implemented to enhance performance, productivity, and create added value for the organization. This research employs a qualitative method with a literature review approach, gathering and analyzing information from various sources relevant to the topics of change management and innovation. The analysis focuses on identifying the symbiotic relationship between the implementation of change management and innovation, and how both influence organizational success in responding to rapid external environmental changes. The results indicate that organizations that effectively implement change management are better equipped to foster internal innovation, ultimately enhancing competitiveness, sustainability, and adaptability to ever-changing market demands. This article provides valuable insights for organizations seeking to strengthen their capacity to manage change and design innovation as a key strategy for long-term growth.